Lead distribution in rice plant leaves planted in Sukawening Village, Jatinangor District, West Bandung Regency, West Java - Ming, Wong Chun; Rahayu, Driyanti; Levita, Jutti (JSFK (Jurnal Sains Farmasi & Klinis), 2022)
Lead is harmful when its amounts in food are higher than the optimum. Plants with high levels of lead may trigger the generation of reactive oxygen species and eventually cell death. Our study aimed to assess lead distribution in rice plant leaves planted in Sukawening Village, Jatinangor District, West Bandung Regency, West Java. The rice plant leaves were collected each month until 4 months. The samples were dried and underwent wet destruction. Visible spectrophotometry with the addition of xylenol orange was employed to identify the lead metal in the samples, followed by a standard addition photometric titration method. Our results indicated that lead was identified in the samples since the plant was 1 month old as proven by the Pb-xylenol orange peak at 580 nm. The level of lead in the rice plant leaves were: 1st month (0.4118 mg/kg); 2nd month (0.5232 mg/kg); 3rd month (0.6206 mg/kg); and 4th month (0.5264 mg/kg). We concluded that the lead level in the rice plants is in the range of that required by the Verdict of the Director General of the National Agency of Drug and Food Control No. 03725/B/SK/89 about the Maximum Limit of Heavy Metal Contamination in Food.Â